Strategic Side-Chain Engineering Approach for Optimizing Thermoelectric Properties of Isoindigo-Based Conjugated Polymers - Yoon, Sang Eun; Shin, So Jeong; Lee, Sang Yeon; Jeon, Gyeong G.; Kang, Hyunwoo; Seo, Hyungtak; Zheng, Jian; Kim, Jong H. (ACS Applied Polymer Materials, 2020)
Strategic side-chain engineering has led to an increase in the power factor of isoindigo-based conjugated polymers (CPs) by an order of magnitude. We investigated the effect of side chains on the electrical properties of doped isoindigo-based CPs and gained insight into structure-electrical property-thermoelectric transport intercorrelation for optimization of thermoelectric CPs. For this study, we designed and synthesized four isoindigo-based polymers having different types of alkyl chains. The size of the alkyl chains significantly affected the crystallinity of the films, which subsequently resulted in different charge carrier mobilities and diffusion efficiencies of the molecular dopant. Amorphous polymers with bulkier alkyl chains promoted efficient dopant diffusion while their carrier mobility was relatively lower than that of crystalline CPs. Systematic characterizations on the structural, electrical, and thermoelectrical properties of the CP films showed a trade-off effect for these side-chain structures for optimization of the thermoelectric effect, and with the optimized structure, we obtained a significantly improved power factor up to 37.8 μW·m-1·K-2. This study suggests that exercising fine control of crystallinity through side-chain modification of the fixed polymer backbone can be a simple but very effective approach to maximizing organic thermoelectric effects of CPs.
Keywords: Amorphous polymers; Based conjugated polymers; Effective approaches; Optimized structures; Side chain modifications; Side chain structure; Thermoelectric properties; Thermoelectric transport; conjugated polymer; dopant diffusion; organic thermoelectric; sequential doping; side-chain engineering